Globalisation, accounting and developing countries. (March 2017) - Hopper, Trevor; Lassou, Philippe; Soobaroyen, Teerooven
Abstract: Accounting is an instrument and an object in globalisation but its impact and manifestation is not uniform across Northern developed countries and Southern developing countries (DCs). This paper reviews contributions on globalisation and its influence on accounting in DCs, and identifies important research gaps. It examines the role of accounting in changing development policies, from state capitalism through neo-liberal market-based to good-governance policies. It then considers specific accounting issues, namely the diffusion of International Accounting Standards (now International Financial Reporting Standards) and how they promote global neo-liberalism; the development of the accounting profession in DCs in the face of competition from Northern global accounting firms and professional associations; accounting issues in state-owned organisations, and privatised and multinational corporations; government accounting reforms and the resurrection of the state in DCs; social and environmental accounting issues; and the rise of non-governmental organisations and their accounting and accountability. The discussion and conclusions reflect on achievements to date and important areas requiring further development.